رؤية تشكيلية وجمالية مستوحاة من طوابع البريد التذكارية كمدخل لاستلهام مشغولة نسيجية معاصرة - محجوب، هدى صبحي مصطفى (جامعة جنوب الوادي, 2022)
يحتوي البحث على مجموعة من المحاور كالتالي: - القيمة الجمالية للمشغولة النسيجية. - الجانب التشكيلي الطابع البريد. - الموضوعات الفنية التي تناولتها طوابع البريد. - بعض مشغولات الطلاب النسيجية المستلهمة من طوابع البريد التذكارية. وقد اتبعت الباحثة المنهج الوصفي التحليلي. ومن نتائج البحث: - إيجاد مداخل تدريسية جديدة لمادة النسيجيات اليدوية تساعد على ابتكار وإنتاج أعمال نسيجيه ذات إبعاد تشكيلية مستحدثة بصياغات فنية جديدة وأساليب تقنية مناسبة، وتوظيفه لإنتاج مشغولة نسيجية معاصرة. التوصيات في ضوء ما تقدم توصي الباحثة بالتالي: - التأكيد على أهمية الرؤية التشكيلية والجمالية المستوحاة من طوابع البريد التذكارية، والاستمرار في بحث الموضوعات والمجالات المختلفة وتطوير المشغولة النسيجية المعاصرة وتطويعها من خلال التجريب. - ضرورة التأكيد على الاستمرار في البحث عن إيجاد مداخل جديدة لدراسة النسيج اليدوي المعاصر والتجريب لتطوير الإمكانات التشكيلية للخامات المتواجدة في البيئة وتطويعها لتتناسب مع التقنيات النسيجية الحديثة والتوسع في دراسة النسيجيات اليدوية وفتح آفاق نحو الابتكار والتجديد. - التوسع في دراسة النسيجيات اليدوية وفتح الآفاق نحو الابتكار والتجديد. The research contains a set of themes as follows: - The aesthetic value of the textile work. - Fine aspect of the postage stamp. - Technical topics covered by postage stamps. Some of the students' textile works inspired by commemorative postage stamps. - The researcher followed the descriptive analytical approach. Among the search results: Finding new teaching approaches to the subject of handmade textiles that help in the creation and production of textile works with new plastic dimensions with new artistic formulations and appropriate technical methods and employing it to produce contemporary textile works. Recommendations: In light of the foregoing, the researcher recommends the following: - Emphasizing the importance of the plastic and aesthetic vision inspired by commemorative postage stamps, and continuing to research different topics and fields, and developing and adapting contemporary textile works through experimentation. - The necessity of emphasizing the continuation of the search for finding new approaches to the study of contemporary handmade weaving and experimentation to develop the plastic capabilities of the materials present in the environment and adapt them to suit modern textile techniques and expand the study of handmade textiles and open horizons towards innovation and renewal. - Expanding the study of handicrafts and opening horizons towards innovation and renewal.
Keywords: الفنون التشكيلية -- المشغولات النسيجية -- القيم الجمالية -- طوابع البريد التذكارية